DISPARITY IN JUDGES’ DECISIONS ON THE CRIME OF AGGRAVATED THEFT (AN ANALYSIS OF DECISION NUMBER 968/PID.B/2025/PN MDN AND DECISION NUMBER 1445/PID.B/2025/PN MDN) - Suko Madioso; Halimatul Maryani (CV. Barokah Publsiher, 2026)
Based on the results of the study, it shows that the form of disparity in the judge's decision in the case of aggravated theft based on decision number 968 / Pid.B / 2025 / PN Mdn and Number 1445 / Pid.B / 2025 / PN Mdn is the difference in sentencing to the defendant, namely a 4-year prison sentence for Defendant M. Irfan and a 5-month prison sentence for Defendant Fasi Duhu Baene. The judge's consideration in deciding the defendant's guilt in decisions number 968 and Number 1445 is appropriate. The suitability of the judge's decision with the provisions of criminal law related to aggravated theft in decisions number 968 and number 1445 has been implemented well and the provision of proportional sanctions is appropriate except in Decision Number 1445 which is less proportional because the Defendant was only sentenced to 5 months in prison.